Intelligent Systems Design and Applications 18th International Conference on Intelligent Systems Design and Applications (ISDA 2018) held in Vellore, India, December 6-8, 2018, Volume 1 - Abraham, Ajith; Cherukuri, Aswani Kumar; Melin, Patricia; Gandhi, Niketa (Advances in Intelligent Systems and Computing, 2020)
XXII, 1158 p. 600 illus., 358 illus. in color.